A Detailed Histologic and Molecular Assessment of the Diffuse Sclerosing Variant of Papillary Thyroid Carcinoma - Chou, Angela; Qiu, Min Ru; Crayton, Henry; Wang, Bin; Ahadi, Mahsa S; Turchini, John; Clarkson, Adele; Sioson, Loretta; Sheen, Amy; Singh, Nisha; Clifton-Bligh, Roderick J; Robinson, Bruce G; et al. (Modern pathology, 2023)
Diffuse sclerosing variant papillary thyroid carcinoma (DS-PTC) is characterized clinically by a predilection for children and young adults, bulky neck nodes, and pulmonary metastases. Previous studies have suggested infrequent BRAF mutation but common RET gene rearrangements. Using strict criteria, we studied 43 DS-PTCs (1.9% of unselected PTCs in our unit). Seventy-nine percent harbored pathogenic gene rearrangements involving RET, NTRK3, NTRK1, ALK, or BRAF; with the remainder driven by BRAF mutations. All 10 pediatric cases were all gene rearranged (P = .02). Compared with BRAF -mutated tumors, gene rearrangement was characterized by psammoma bodies involving the entire lobe (P = .038), follicular predominant or mixed follicular architecture (P = .003), pulmonary metastases (24% vs none, P = .04), and absent classical, so-called "BRAF-like" atypia (P = .014). There was no correlation between the presence of gene rearrangement and recurrence-free survival. Features associated with persistent/recurrent disease included pediatric population (P = .030), gene-rearranged tumors (P = .020), microscopic extrathyroidal extension (P = .009), metastases at presentation (P = .007), and stage II disease (P = .015). We conclude that DS-PTC represents 1.9% of papillary thyroid carcinomas and that actionable gene rearrangements are extremely common in DS-PTC. DS-PTC can be divided into 2 distinct molecular subtypes and all BRAF -negative tumors (1.5% of papillary thyroid carcinomas) are driven by potentially actionable oncogenic fusions.